Dewi Saraswati Masa Kini: Peran Perempuan Dalam MemajukanPendidikan Agama Hindu (Haridracarya: Journal of Hindu Religious Education, 2024)
Goddess Saraswati in Hinduism is symbolized as the goddess of knowledge. The meaning of Saraswati is described as a goddess or beautiful woman who has beauty, intelligence and a flow of knowledge. This symbol has become an icon that is widely spread in society in advancing education, especially for women. This article focuses on the role of women today who adopt the majestic values ​​of the goddess Saraswati who never stops providing knowledge guidance, especially regarding Hindu religious education. The focus is on highlighting their contribution to women's efforts, especially in the field of formal and non-formal education, also related to the preservation of their culture. This is interesting to study because what we observe is that the role of women in Hindu society has undergone a transformation, which was previously more limited by rules or social norms. Now they show great potential in creating positive change. Women as the embodiment of the goddess Saraswati are able to play a role in advancing Hindu religious education and strengthening cultural identity in the era of globalization
Keywords: Goddess Saraswati; Role of Women; Advancing Hindu Religious Education.